1988
DOI: 10.1007/bf00547165
|View full text |Cite
|
Sign up to set email alerts
|

The sequelae of Osgood-Schlatter's disease in adults

Abstract: Seven adults with the sequelae of Osgood-Schlatter's disease presented after experiencing symptoms for an average of eight years. In four cases a true joint had formed between an ossicle in the patellar ligament and a facet on the tibia. Surgical treatment produced good results in all of the patients. Treatment differs from that in children in whom the epiphyseal lines are open.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
8
0
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 7 publications
0
8
0
1
Order By: Relevance
“…Nevertheless, not all cases of Osgood-Schlatter disease will resolve completely at maturity. [6][7][8][9][10][11] In a review of the natural history of untreated Osgood-Schlatter disease, Krause and coworkers 8 have found that 76% of patients thought they had no limitation of activity; however, only 60% could kneel without discomfort. It is expected that the continued symptoms of Osgood-Schlatter disease in adulthood may be more evident and more disabling in the populations who require prolonged hyperflexion of the their knees or kneeling due to religious, social, or employment causes.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Nevertheless, not all cases of Osgood-Schlatter disease will resolve completely at maturity. [6][7][8][9][10][11] In a review of the natural history of untreated Osgood-Schlatter disease, Krause and coworkers 8 have found that 76% of patients thought they had no limitation of activity; however, only 60% could kneel without discomfort. It is expected that the continued symptoms of Osgood-Schlatter disease in adulthood may be more evident and more disabling in the populations who require prolonged hyperflexion of the their knees or kneeling due to religious, social, or employment causes.…”
Section: Discussionmentioning
confidence: 99%
“…9 However, most authors found a lower incidence of separate ossicle in their patients, ranging from 50 to 70%. [6][7][8] Woolfrey and Chandler noted that the shape of tibial tubercle was more irregular in their older age group of patients. 6 The difference between the more advanced pathology in our series compared with other studies may be related to the older age of our patients.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations